A Question of Laser Intensity. Issue 4 (1994) - McRae, G. A.
Abstract : Parameterization of laser intensity requires different practical definitions which depend on the temporal and spatial characteristics of the optical beam. Comparison of observations obtained using different lasers, with similar numerical values of intensity, will prove misleading for non-linear phenomena. The invariant quantities that each experiment should have in common are the determinable model parameters.